Narrating organised crime stories and Aristotelian principles of drama - Duyne, Petrus C. van 1946-; Larsson, Paul; Harvey, Jackie 1958-; Lampe, Klaus von 1961-; Antonopoulos, Georgios ca. 20./21. Jh (Eleven, 2022)
This volume contains the contributions of the 21st Cross-Border Crime Colloquium webinar hosted by the Norwegian Police University College, Kongsvinger and organised 22-24 August 2021. Despite the pandemic, the Colloquium Group decided to return to the 'criminal normal' and the related research on (cross-border) organised crime, corruption, labour exploitation, fraud, ecological crime and the search for criminal revenues. These are partly old themes, some getting renewed attention, such as the hidden wealth of corrupt political elite, whether Nigerian godfathers or Russian oligarchs.00A criminal theme with global implications is the growing ?green-criminality? or crime against the nature. Forests are illegally cut clear in Eastern Europe to satisfy the hunger of the European furniture industry: cheap furniture from stolen wood from the Carpathian or further east leaving behind devastated landscapes. Also, criminal waste trafficking from industrialised farming finding its way through criminal channels is a recognised cross-border organised crime.00In peer reviewed contributions international experts present a broad range of criminal phenomena and policies: from a 25-year review of organised crime in The Czech Republic, labour exploitation and Nigerian organised crime in Italy, Middle-Eastern criminal clans in Germany, and international fuel fraud to criminal asset recovery policy in the Netherlands
Keywords: Aristoteles -- v384-v322; Organisiertes Verbrechen; Dramentheorie; Organized crime; Aristotle / Influence; Konferenzschrift -- 2021